Morphological, Cultural, Pathological and Molecular Variability among Fusarium oxysporum f.sp. zingiberi isolates - Gupta, Meenu; Jarial, Kumud; Vikram, Amit (International Journal of Bio-resource and Stress Management, 2023)
Nineteen isolates of Fusarium oxysporum f.sp. zingiberi causal organism of Fusarium yellows in ginger were collected from different ginger growing areas of Himachal Pradesh and designated as I1 to I19. Morphological variations with respect to mycelial colour, conidial size and formation of chlamydospores and pathogenic variation in terms of disease incidence among different isolates was studied in these isolates. The mycelial colour varied from white to dull white with slightly pinkish tinge. The microconidial size varied from 5.20×4.00 μm (I8) to 12.30×5.70 μm (I3) whereas macroconidial size varied from 16.20×4.70 μm (I7) to 32.0×5.70 μm (I4). Chlamydospore dimensions also varied in all the nineteen isolates of the test pathogen. All isolates formed chlamydospores on PDA medium. Pathogenic variability revealed that lesion size varied from 8.50 to 18.00 mm after 10 days of inoculation whereas, incubation period varied from 11 to 19 days. Genetic variation was also analysed by using forty 10 – mer oligonucleotide RAPD primers, out of which 2 primers yielded informative, strong and reproducible DNA amplicons of Fusarium oxysporum f.sp. zingiberi and thus were selected for studying the variation among isolates. The dendrogram of DNA fingerprints revealed 0 to 80% variation among isolates. All isolates were grouped into two different major groups each comprising of ten and nine isolates, respectively.